Abordagens sintéticas visando a preparação de bacterioclorinas de alta conjugação - Assis, Francisco Fávaro de (Universidade Federal de São Carlos, 2016)
Bacteriochlorins are porphyrin derivatives containing two reduced peripheral double bonds (FIGURE 1). These compounds present, as their main properties, intense absorption bands close to the Near Infrared (NIR, 750-900 nm) (FIGURE 1). Such properties make then attractive for studies in photomedicine, solar devices and many others. Since the beginning, this research was focused in the synthesis of new bacteriochlorin derivatives, thus containing conjugated chromophore groups at non-reduced  positions, in order to redshift the absorption bands into the NIR... continues in the text
Synthetic approaches aiming at the preparation of high conjugated bacteriochlorins
Keywords: Síntese orgânica; Bacterioclorinas; Acoplamento cruzado; Infravermelho próximo; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA